2022
DOI: 10.5851/kosfa.2022.e16
|View full text |Cite
|
Sign up to set email alerts
|

Development of Temperature Control Algorithm for Supercooling Storage of Pork Loin and Its Feasibility for Improving Freshness and Extending Shelf Life

Abstract: Supercooling storage refers to lowering the product temperature below its freezing point without phase transition and has the potential to extend shelf life. Nevertheless, supercooled objects are in a thermodynamically unstable state, and nucleation can occur spontaneously. To achieve supercooling storage, slow cooling and insulation are essential. Hence, a stepwise algorithm for the supercooling storage of pork loins was designed and validated in this study. Pork loins were stored at 3°C, −18°C, and −3°C (fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…For supercooled beef, there was no evidence of meat freezing for the whole storage period ( Figure 2 B). Based on a preliminary study, beef loin was more stable for supercooling preservation than pork or fish; hence, the present study adopted −3.5 °C as the lowest temperature, which was lower than previous investigations [ 1 , 5 ]. The temperature of the supercooling group showed a limited fluctuation due to the utilization of an EPS box.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For supercooled beef, there was no evidence of meat freezing for the whole storage period ( Figure 2 B). Based on a preliminary study, beef loin was more stable for supercooling preservation than pork or fish; hence, the present study adopted −3.5 °C as the lowest temperature, which was lower than previous investigations [ 1 , 5 ]. The temperature of the supercooling group showed a limited fluctuation due to the utilization of an EPS box.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, quality deteriorations involved in the physical tissue damage of meat were inevitably manifested even if ultrafast freezing was applied [ 3 ], and current novel techniques have been focused on preservation at subzero temperatures without the freezing of meat [ 2 , 4 ]. Supercooling is considered as a representative novel technique that can extend the shelf life and wholesomeness of meat by 2–3 weeks [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle fiber characteristics are reference traits that determine meat quality. They also provide basic information that can be applied to choose optimal storage or processing methods [ 4 , 40 , 41 ]. For example, when refrigerating or freezing pork, taking into consideration the histological and physicochemical characteristics of each meat part can improve meat quality or prevent quality deterioration [ 9 , 10 ].…”
Section: Post-harvest Strategies For Controlling Meat Qualitymentioning
confidence: 99%
“…For example, when refrigerating or freezing pork, taking into consideration the histological and physicochemical characteristics of each meat part can improve meat quality or prevent quality deterioration [ 9 , 10 ]. In general, considerable effort is being made to identify excellent technologies for packaging and storing (aging) meat [ 35 , 40 - 42 ], and a deeper understanding of the muscle fiber characteristics of each muscle type or meat cut will make this process easier. Previous studies conducted from this perspective have shown that FG muscle fibers are more vulnerable to freezing than SO muscle fibers [ 9 , 10 ].…”
Section: Post-harvest Strategies For Controlling Meat Qualitymentioning
confidence: 99%
“…The most widely used technique for achieving supercooling in food and biological materials is to cool them slowly, which ensures that the temperature at different locations in the food is consistent, thus achieving the effect of supercooling (Charoenrein & Preechathammawong, 2010). Based on slow freezing, supercooling preservation of some vegetables, meat, and organs has been realized (Fukuma et al, 2012;Lee et al, 2022;Park et al, 2022;Sultana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%